2011
DOI: 10.3851/imp1918
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Antiretroviral Drugs in Anatomical Sanctuary Sites: The Fetal Compartment (Placenta and Amniotic Fluid)

Abstract: HIV resides within anatomical 'sanctuary sites' where local drug exposure and viral dynamics may differ significantly from the systemic compartment. Widespread implementation of antiretroviral therapy has seen a significant decline in the incidence of mother-to-child transmission (MTCT) of HIV. In addition to suppression of maternal plasma/genital viral loads, antiretroviral agents that cross the placenta and achieve adequate concentrations in the fetal compartment may exert a greater prophylactic effect. Pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 107 publications
4
34
0
1
Order By: Relevance
“…Low concentration ratios for EVG and DTG were noted between cord plasma and placenta, cord plasma and maternal plasma, and cord PBMCs and maternal PBMCs. There are limited PK data on placental transfer of EVG (4)(5)(6)(7)(8). Distributions of all five drug concentrations for all the matrices were analyzed and are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Low concentration ratios for EVG and DTG were noted between cord plasma and placenta, cord plasma and maternal plasma, and cord PBMCs and maternal PBMCs. There are limited PK data on placental transfer of EVG (4)(5)(6)(7)(8). Distributions of all five drug concentrations for all the matrices were analyzed and are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CLI values reported using this ex vivo placental perfusion model were 40.3% for darunavir (18) and 73% for lopinavir at a 2% serum albumin concentration (19), whereas there was nearly no placental transfer for saquinavir (10). For the nucleoside reverse transcriptase inhibitors, the fetal concentrations were equal to or higher than the maternal concentrations (20), whereas the CLI of the CCR5 inhibitor maraviroc was 26%, and the fusion inhibitor enfuvirtide did not cross the placenta (21). This ex vivo model does have important limitations.…”
Section: Rilpivirine (4-[[4-[[4-[(e)-2-cyanoethenyl]-26-dimethylphenmentioning
confidence: 92%
“…[32][33][34][35] Nevirapine attains nearly equivalent concentrations in maternal and umbilical cord blood, and concentrations in amniotic fluid are roughly 75.0% of those in maternal blood. 36,37 Limited data exist on efavirenz. Placental transfer of etravirine has been documented in rats, and animal studies have not demonstrated any harmful teratogenic effects.…”
Section: Etravirine In Pregnancymentioning
confidence: 99%
“…Placental transfer of etravirine has been documented in rats, and animal studies have not demonstrated any harmful teratogenic effects. 36 Furco et al described a 38-yearold woman with multidrug-resistant HIV and pregnant with a twin gestation who received etravirine 200 mg twice daily beginning at 25 weeks' gestation in combination with darunavir, ritonavir, and enfuviritide. 38 Her HIV RNA viral load improved from 4,660 copies/mL to ,50 copies/mL, while her CD4 count decreased from 471 cells/µL to 356 cells/µL.…”
Section: Etravirine In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation